PENGARUH GENDER, ETHICAL SENSITIVITY, DAN LOCUS OF CONTROL TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI (Studi pada Universitas Islam Batik Surakarta) - Wulandari Wulandari; Rispantyo Rispantyo; Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This research is meant to test the influence to the gender, ethically sensitivity, and the locus of control to the ethically behavior of the accounting students at University of Islam Batik Surakarta. Data retrieval is done by distributing questionnaires to 85 students majoring in accounting at The University of Islam Batik Surakarta. The sampling technique used was purposive sampling. Data quality was tested by using test validity and reliability testing. The analysis tool used is multiple regression test using the F test and T test simultaneous partial. The results of this study indicate that there is no gender influence on ethical behavior of accounting students, ethical sensitivity and locus of control affect the ethical behavior of accounting students.